2020
DOI: 10.2196/21369
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Screening via Deep Learning Using a Combination of Epidemiological and Patient-Generated Health Data: Development and Validation Study

Abstract: Background Screening for influenza in primary care is challenging due to the low sensitivity of rapid antigen tests and the lack of proper screening tests. Objective The aim of this study was to develop a machine learning–based screening tool using patient-generated health data (PGHD) obtained from a mobile health (mHealth) app. Methods We trained a deep learning model based on a gated recurrent unit to scre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…These studies were also limited because performance outside the health care system of the University of Pittsburgh was unknown. More recently, a Korean study reported an influenza screening system based on deep learning using a combination of epidemiological and patient-generated health data from a mobile health app [22]. However, the gold standard in the study was the clinical diagnosis of influenza at a clinic reported by app users instead of laboratory-based confirmed influenza.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies were also limited because performance outside the health care system of the University of Pittsburgh was unknown. More recently, a Korean study reported an influenza screening system based on deep learning using a combination of epidemiological and patient-generated health data from a mobile health app [22]. However, the gold standard in the study was the clinical diagnosis of influenza at a clinic reported by app users instead of laboratory-based confirmed influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several AI-assisted diagnostic prediction models have been proposed for influenza diagnosis [19][20][21][22]. A single-center study from Japan reported a machine learning-based infection screening system incorporating a random tree algorithm that used vital signs [19].…”
Section: Clinical Characteristics Associated With Pcr-confirmed Influ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Xia et al reported an AI-based classifier distinguishing influenza from COVID-19 using chest X-ray images and clinical features with an AUC of 0.9 [ 17 ]. Choo et al reported the usefulness of the patient-generated health data obtained from a mobile health application to develop an AI-based screening tool for influenza [ 18 ]. However, Japan has lagged behind other countries in introducing such mobile health applications based on smartphones or smartwatches [ 19 ].…”
Section: Discussionmentioning
confidence: 99%